MODERN APPROACHES AND INTERNATIONAL CLINICAL STANDARDS IN ANESTHESIOLOGY - Yusupova Nixola Shavkatovna (Modern American Journals, 2025)
This article analyzes modern international standards in anesthesiology based on ASA, ESAIC and WFSA guidelines. Current practices such as perioperative risk assessment, depth-of-anesthesia monitoring, multimodal analgesia, goal-directed therapy, lung-protective ventilation, and low-flow anesthesia are evaluated. The effectiveness of ERAS protocols and their impact on postoperative outcomes is highlighted. The paper is prepared in accordance with international scientific publication requirements and is suitable for OAK/Scopus-indexed journals.
Keywords: anesthesiology, perioperative medicine, multimodal analgesia, BIS monitoring, ERAS, low-flow anesthesia, hemodynamics, ventilation.